Identifying and Treating Uterine Disease in Dairy Cows - Klibs N. Galvão; Carlos Risco; Jose E.P. Santos (EDIS)
Uterine diseases are prevalent in high producing dairy cows and require prompt diagnosis and treatment. This 6-page fact sheet describes identification and treatment for four classes of uterine diseases in dairy cows. Written by Klibs N. Galvão, Carlos Risco, and Jose E.P. Santos, and published by the UF Department of Veterinary Medicine, May 2011.